Determine the Prevalence and Factors Contributing to Increase the Caesarean Section Rate amongst post-partum women at Lyari Town Karachi, Pakistan - Sameer Ali, Shahla Parhan; Yasin, Muhammad; Ali Khan, Shahid; Rasheed Bhatti, Shabana; Fatima, Eshrat; Aziz, Tariq (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine the prevalence and factors contributing to the increase in the Cesarean Section Rate among Post-Partum Women in Two Private Hospitals in Lyari Town, Karachi, Pakistan. Methodology: A descriptive cross-sectional study was conducted from August to November 2022 after getting approval from the Institutional Review Board (IRB) of Kharadar General Hospital. The purposive sampling technique and self-structured questionnaires were used to achieve the sample size of 230 post-partum women with age < than 45 were included in the study whereas Women who were delivered vaginally, and those who were not willing were excluded in this research criteria and the data was analyzed by using SPSS V-16 software. Results: The results showed that CSR was more observed between the ages of (26-35) (56%), and were mainly housewives (71.3%), matriculated (47.8%), and belonged to the Balochis family. As, CSR has drastically increased in Lyari Town Karachi, Pakistan (33%), and the rate of Planned Cesarean Section (CS) (63%) exaggerated more than an Emergency CS (37.4%).Scarred Uterus (32.1%) being an obstetrical factor, while Patient Preferences (30.4%) being a non-obstetrical factor were the most common reasons for Planned C-Section. Fetal Distress (33.9%) and Polyhydramnios (11.3%) were the reasons for an Emergency C-Section. Labor anxiety also influenced cesarean section. Besides, smokeless tobacco (Pan, Ghutka, Chalia, and Supari), (18% to 23%) was also identified as contributing factor among women. Practical Implication: The study found a strong correlation between Corporate Social Responsibility (CSR) and demographic factors and medical practices, particularly among women aged 26-35. In Karachi, Pakistan, CSR activities increased significantly. Women prefer Planned Cesarean Sections over Emergency Cesarean Sections, with scarred uterus and patient preferences being primary reasons. Conclusion: Planned CS is increasing unnecessarily in the health care setting, and this could be reduced by offering written guidelines, policy development, monthly medical audits, and advised CS when there is a medical necessity.